2019
DOI: 10.3390/rs11070866
|View full text |Cite
|
Sign up to set email alerts
|

Onboard Radio Frequency Interference as the Origin of Inter-Satellite Biases for Microwave Humidity Sounders

Abstract: Understanding the causes of inter-satellite biases in climate data records from observations of the Earth is crucial for constructing a consistent time series of the essential climate variables. In this article, we analyse the strong scan- and time-dependent biases observed for the microwave humidity sounders on board the NOAA-16 and NOAA-19 satellites. We find compelling evidence that radio frequency interference (RFI) is the cause of the biases. We also devise a correction scheme for the raw count signals fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…A dedicated study presented in a different article [32] revealed that also AMSU-B on NOAA-16 and even MHS on NOAA-19 suffer significantly from RFI. RFI was identified as the main reason for the strong inter-satellite biases that are observed for channels 3-5 for AMSU-B on NOAA-16 and 3 and 4 for MHS on NOAA-19.…”
Section: Radio Frequency Interference (Rfi)mentioning
confidence: 99%
“…A dedicated study presented in a different article [32] revealed that also AMSU-B on NOAA-16 and even MHS on NOAA-19 suffer significantly from RFI. RFI was identified as the main reason for the strong inter-satellite biases that are observed for channels 3-5 for AMSU-B on NOAA-16 and 3 and 4 for MHS on NOAA-19.…”
Section: Radio Frequency Interference (Rfi)mentioning
confidence: 99%
“…Channel H3 on NOAA‐19, however, was affected by radio‐frequency interference, and the correction scheme by Hans et al. (2019) only works for Earth view counts. Therefore, we excluded these data from our calculations and decided to plot the average of channels H4 and H5 in Figure 5 as a way to reduce the scatter of points.…”
Section: Resultsmentioning
confidence: 99%
“…All sounding channels of AMSU-B and MHS provide the radiance of the Moon very close to 183.31 GHz with the exception of channel H5 on MHS, which operates at 190.31 GHz. Channel H3 on NOAA-19, however, was affected by radio-frequency interference, and the correction scheme by Hans et al (2019) only works for Earth view counts. Therefore, we excluded these data from our calculations and decided to plot the average of channels H4 and H5 in Figure 5 as a way to reduce the scatter of points.…”
Section: Brightness Temperature Of the Waxing And Waning Moonmentioning
confidence: 99%
“…This can explain the emerging scan-and time-dependent biases, since the effect of RFI is both scan-and time-dependent. An RFI correction was applied in the FIDUCEO FCDR to all three instruments 39 , which was shown to improve the consistency between instruments. However, for NOAA15 and NOAA17 only an early version of the correction scheme could be applied due to the lack of a reference month that is not affected by RFI.…”
Section: Comparison To the Cm-saf Uth Cdr To Validate The Fiduceo Utmentioning
confidence: 99%
“…Combined, the weaker decrease of NOAA17 UTH and the stronger decrease of NOAA16 UTH due to the near-nadir pixel selection result in a larger bias between NOAA16 and NOAA17 in UTH FID than in UTH CMSAF . The instruments onboard NOAA15, NOAA16 and NOAA17 are known to suffer from radio frequency interference (RFI) from transmitters on-board the satellite 37 39 . This can explain the emerging scan- and time-dependent biases, since the effect of RFI is both scan- and time-dependent.…”
Section: Technical Validationmentioning
confidence: 99%